Organic resin coated steel sheet
The organic resin-coated steel sheet addresses press formability and weldability issues by controlling film thickness and composition, ensuring excellent sliding properties and film removability for complex automotive applications.
Patent Information
- Application Number
- JP2023523275
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-11
- Filing Date
- 2023-01-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-01-27
AI Technical Summary
Existing steel sheets face challenges in achieving sufficient press formability for complex molding, mold galling, and maintaining weldability and film removability during automotive applications, particularly in processes involving severe drawing and continuous press forming.
A steel sheet coated with an organic resin film, controlled to have an average coating weight of 0.2-2.0 g/m² and an area ratio of thin film portions of 25.0% or less, utilizing a combination of acrylic, urethane, or phenol resins with hydrocarbon wax, and an anionic polymer dispersant, to enhance sliding properties and maintain film removability and weldability.
The organic resin-coated steel sheet exhibits excellent press formability, reduced friction with molds, stable performance under high contact pressure, and maintains film removability and weldability, suitable for complex automotive components.
Smart Images

Figure 0007616365000003 
Figure 0007616365000004 
Figure 0007616365000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel sheet having excellent sliding properties in press forming, and in particular to a steel sheet having an organic resin film which has excellent formability even in severe drawing, can be removed with an alkali, and has excellent weldability. [Background technology]
[0002] Cold-rolled steel sheets and hot-rolled steel sheets are widely used in a wide range of fields, mainly for automobile body applications, and in such applications, they are subjected to press forming before use. In recent years, there has been a demand for the integration of parts to reduce processes and for improved design, making it necessary to enable more complex forming. If more complex press forming is attempted, there is a possibility that the steel sheet will not be able to withstand the forming and break, or that die galling will occur during continuous press forming, which could have a serious adverse effect on automobile productivity. Therefore, it is necessary to improve the press formability of steel sheets.
[0003] One method for improving the press formability of cold-rolled steel sheets and hot-rolled steel sheets is to perform a surface treatment on the die. Although this method is widely used, the die cannot be adjusted after the surface treatment. In addition, this method has problems such as high costs. Therefore, there is a strong demand for improving the press formability of the steel sheet itself.
[0004] One method to improve press formability without surface treatment of the die is to use a high viscosity lubricant, but this can lead to poor degreasing after press forming, which can lead to poor paintability.
[0005] In response to this, various types of lubricant surface-treated steel sheets have been investigated as a technology that enables press forming without the need for surface treatment of dies or high-viscosity lubricants.
[0006] Patent Document 1 describes a technique for forming a lubricating film, which is an acrylic resin film containing synthetic resin powder, on a zinc-plated steel sheet.
[0007] Patent Document 2 describes a technique for forming a lubricating film on a steel sheet, which comprises lithium silicate as a film component and wax and metal soap as lubricants.
[0008] Patent Document 3 describes a lubricating surface-treated metal product having excellent press formability, which is coated with a 0.5 to 5 μm thick film made of polyurethane resin containing a lubricant.
[0009] Patent Document 4 describes a technique for forming an alkali-soluble organic film, which is an epoxy resin containing a lubricant added thereto, on a steel sheet. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 9-170059 [Patent Document 2] JP 2002-307613 A [Patent Document 3] JP 2000-309747 A [Patent Document 4] JP 2000-167981 A Summary of the Invention [Problem to be solved by the invention]
[0011] However, in Patent Documents 1 to 4, although lubricity is achieved by the lubricating effect of the lubricant contained therein, press moldability is not necessarily sufficient in complex molding.
[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide an organic resin-coated steel sheet that has low sliding resistance in areas at risk of cracking during press forming and has excellent press formability in areas where the surface pressure is high and mold galling is expected to occur, for steel sheets that are subjected to complex forming processes that are difficult to press form.
[0013] In addition, when used as a steel sheet for automobiles, it is also required to have a coating-removable property applicable to the alkaline degreasing step in the painting process, and further, excellent weldability. In such applications, it is a further object to have both applicable coating-removable property and excellent weldability. [Means for solving the problem]
[0014] In order to solve the above problems, the present inventors focused on the relationship between the film thickness uniformity of a coating formed on a steel sheet and the sliding characteristics (press formability) during press forming, and after extensive research, obtained the following findings.
[0015] When a steel plate having an organic resin coating on its surface slides against a die, the coating component is supplied between the steel plate and the die. Since the coating component is more susceptible to shear deformation than the steel plate, it is considered that the coating component supplied between the steel plate and the die acts as a lubricant, improving the sliding characteristics. On the actual steel plate surface, there are fine irregularities caused by rolling or the like. When the steel plate slides against the die, the convex parts of the steel plate come into contact with the die, generating sliding resistance. Paint containing organic resin coating components tends to accumulate in the concave parts of the steel plate between the application and the coating drying process, forming a thick coating, and the organic resin coating on the convex parts tends to become thin. If the coating properties of the organic resin coating are poor and a coating with a sufficient thickness is not formed on the convex parts, the coating components are not sufficiently supplied between the steel plate and the die, and the effect of improving the sliding characteristics is reduced. Therefore, it was found that in order to improve the sliding characteristics between the steel plate and the die, it is necessary to apply an organic resin coating with excellent organic resin coating properties to the steel plate.
[0016] As a result of extensive investigations into the above organic resin film coverage, it was found that the organic resin film coverage can be evaluated by measuring the area ratio of thin film portions (area ratio of thin film portions) of the steel sheet protrusions. Here, we found that it is effective to determine the thin film portion by using a Schottky field emission SEM equipped with an energy dispersive X-ray spectrometer and determining that the area in the characteristic X-ray image has an intensity below a certain level as the thin film portion.
[0017] In addition, the local adhesion amount calculated using the above method was 0.14 g / m2 It was discovered that when the thin film portion described below accounts for 25.0% or less of the entire observation surface, press formability (sliding characteristics) is excellent. Furthermore, the components, composition and properties of the organic resin film were examined to find the optimum conditions for making the thin film portion 25.0% or less of the entire observation surface.
[0018] The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] At least one side is coated with an organic resin film, with an average coating weight of 0.2 g / m per side after drying. 2 More than 2.0g / m 2 A steel sheet coated as follows: The organic resin film had a coating weight of 0.14 g / m 2 The organic resin-coated steel sheet has an area ratio of 25.0% or less of the thin film portion as described below. [2] The average area of the thin film portion is 10.0 μm 2 The organic resin-coated steel sheet according to [1], [3] The organic resin-coated steel sheet according to [1] or [2], wherein the area ratio of the thin film portion is calculated by the following methods (1) and (2). (1) At an accelerating voltage of 5 kV or more and 20 kV or less, an X-ray image characteristic of the CK line on the surface of the organic resin-coated steel sheet is taken by an X-ray spectrometer mounted on an SEM. (2) The local adhesion amount was 0.14 g / m from the characteristic X-ray image of CK rays. 2 The area below the threshold intensity corresponding to is defined as the thin film portion, and the area above the threshold intensity is defined as the non-thin film portion. The area of the thin film portion is defined as the area of the thin film portion / (area of the thin film portion+area of the non-thin film portion)×100%. [4] The organic resin-coated steel sheet according to any one of [1] to [3], wherein the organic resin coating is a coating containing at least one of acrylic resin, urethane resin, and phenol resin. [5] The organic resin-coated steel sheet according to any one of [1] to [4], wherein the organic resin coating contains 50 mass % or less of wax based on the total coating weight. [6] The organic resin-coated steel sheet according to [5], wherein the wax is a hydrocarbon-based wax. [7] An organic resin-coated steel sheet according to [5] or [6], wherein the average particle size of the wax is 0.01 μm or more and 4 μm or less. [8] The organic resin-coated steel sheet according to any one of [5] to [7], wherein the organic resin coating contains 5.0 mass % or less of an anionic polymer-type dispersant based on the total coating weight.
[0019] In the present invention, the steel sheet refers to a hot-rolled steel sheet and a cold-rolled steel sheet. Effect of the Invention
[0020] According to the present invention, an organic resin-coated steel sheet having excellent press formability can be obtained. The coefficient of friction between the organic resin-coated steel sheet and a die or the like is significantly reduced. As a result, the steel sheet has stable and excellent press formability for a relatively low-strength steel sheet that is subjected to complex forming. Furthermore, even for a high-strength steel sheet that is subjected to increased surface pressure during press forming, a steel sheet having low sliding resistance at a portion at risk of cracking during press forming and excellent press formability at a portion where surface pressure is high and die galling is expected to occur can be obtained. Furthermore, there is no impediment to subsequent processes such as welding, degreasing, chemical conversion treatment, and painting.
[0021] It was also confirmed that the organic resin-coated steel sheet of the present invention has a film-removing property that allows it to be applied to an alkaline degreasing step in a painting process when used as a steel sheet for automobiles. Furthermore, it was confirmed that the organic resin-coated steel sheet of the present invention has excellent weldability.
[0022] In the above, "high strength" refers to a tensile strength (TS) of 440 MPa or more, and "relatively low strength" refers to a TS of less than 440 MPa. [Brief description of the drawings]
[0023] [Figure 1] This is an example of a characteristic X-ray image (CK line) of an organic resin-coated steel sheet. [Diagram 2] FIG. 2 is a schematic front view showing a friction coefficient measuring device. [Diagram 3] FIG. 3 is a schematic perspective view showing the shape and dimensions of the bead in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, an embodiment of the present invention will be described.
[0025] The organic resin-coated steel sheet of the present invention is a steel sheet having a surface coated with a resin or an organic film containing a resin and wax as appropriate. A paint in which a resin is dissolved or dispersed in a solvent, or a paint in which wax is added to either of these, is applied to the surface of the steel sheet and dried.
[0026] First, the reason why the coverage of the organic resin film affects the sliding characteristics during press molding will be explained below, along with the coverage of the organic resin film.
[0027] At least one side of the steel sheet is coated with an organic resin film, with the average coating weight per side after drying being 0.2 g / m 2 More than 2.0g / m 2 The reasons for limiting it to the following are as follows.
[0028] Average adhesion weight per side after drying is 0.2g / m 2 If the average adhesion weight per side after drying is less than 0.2 g / m, sufficient press formability cannot be obtained. 2 More than 0.5g / m 2 It is preferable that the thickness is 1.0 g / m or more. 2 On the other hand, the average coating weight is preferably 2.0 g / m or more. 2 If the average adhesion weight of the organic resin film after drying exceeds 2.0 g / m, the weldability and removability may deteriorate. 2 In the case of more than 0.14 g / m2, the localized adhesion amount is 0.14 g / m2. 2 Therefore, there is an advantage that the deterioration of sliding properties due to the increase in the area ratio of the thin film portion, which is the subject of the present application, is unlikely to occur. However, taking into consideration the above-mentioned disadvantages (deterioration of weldability and removal of the coating), the average coating weight is set to 2.0 g / m 2 The amount of adhesion locally is 0.14g / m or less. 2 The increase in the area ratio of the thin film portion below the average coating weight of 1.4 g / m2 This problem is particularly evident in the following cases, resulting in a significant deterioration in sliding properties. By using the method for making the film thickness uniform according to the present invention, such deterioration in sliding properties is significantly improved. Therefore, the method for making the film thickness uniform according to the present invention is effective in improving the average coating weight of the organic resin film when the average coating weight is 1.4 g / m 2 It is particularly suitable for use with organic resin-coated steel sheets having a coating thickness of 1.2 g / m 2 It is more preferred to apply:
[0029] Next, we explain the reason why the coverage of the organic resin film affects the sliding characteristics during press molding, and then we explain the adhesion weight of the organic resin film when it is 0.14 g / m 2 The reason why the area ratio of the thin film portion is 25.0% or less will be explained below.
[0030] When a steel sheet having an organic resin coating on its surface slides against a die, the coating components are supplied between the steel sheet and the die. Since the coating components are more susceptible to shear deformation than the steel sheet, it is believed that the coating components supplied between the steel sheet and the die act as a lubricant, improving the sliding characteristics. On the actual steel sheet surface, fine irregularities are present due to rolling or the like. When the steel sheet slides against the die, the convex parts of the steel sheet come into contact with the die, generating sliding resistance. Paint containing organic resin coating components tends to accumulate in the concave parts of the steel sheet between the application and the coating drying process, forming a thick coating, and the organic resin coating on the convex parts tends to become thin. If the coating properties of the organic resin coating are poor and a coating with a sufficient thickness is not formed on the convex parts, the coating components are not sufficiently supplied between the steel sheet and the die, and the effect of improving the sliding characteristics is reduced. Therefore, in order to improve the sliding characteristics between the steel sheet and the die, it is necessary to apply an organic resin coating with excellent organic resin coating properties to the steel sheet. Therefore, the adhesion amount of the organic resin coating is 0.14 g / m 2 The area ratio of the thin film portion must be 25.0% or less. The area ratio of the thin film portion is preferably 20.0% or less. More preferably, it is 15.0% or less. On the other hand, the lower the area ratio of the thin film portion, the more improved the organic resin film coverage is, so the lower limit is not particularly limited and may be 0%.
[0031] Furthermore, the average area of the thin film portion is 10.0 μm 2The reason for this is that, as described above, if a coating of sufficient thickness is not formed on the protruding portions, the coating components are not sufficiently supplied between the steel sheet and the die, and the effect of improving the sliding characteristics is reduced. Therefore, it is preferable to set the average area of the thin film portion to 10.0 μm or less. 2 It is preferable to set the thickness to 9.5 μm or less. 2 More preferably, it is 9.0 μm or less. 2 On the other hand, the lower the average area of the thin film portion, the more improved the organic resin film coverage is, so the lower limit is not particularly limited, and is preferably 0 μm or less. 2 It may be.
[0032] The average thickness of the organic resin film is not particularly limited, but is preferably 0.2 μm or more and 2.0 μm or less.
[0033] The area ratio of the thin film part of the organic resin film is 25.0% or less, and the average area of the thin film part is 10.0 μm 2 The following control methods include controlling the viscosity of the paint within a certain range. If the viscosity is too low, the paint will tend to accumulate in the recesses, causing the liquid film thickness on the protrusions to become thin, resulting in a thin film area ratio exceeding 25.0%, or the liquid film thickness on the protrusions to become uneven, resulting in an average thin film area of 10.0 μm. 2 The viscosity of the paint will exceed this limit. Therefore, it is necessary to make the viscosity of the paint above a certain value. For this reason, it is preferable for the viscosity of the paint to be 1.5 mPa·s or more. On the other hand, if the viscosity of the paint is too high, the paint will be applied unevenly, and streaks and other patterns will appear after the film is formed, resulting in a poor appearance. Therefore, it is necessary to make the viscosity of the paint below a certain value. For this reason, it is preferable for the viscosity of the paint to be 8.0 mPa·s or less.
[0034] In addition, if the drying time of the coating is long, the paint spreads during the drying process and tends to accumulate in the recesses, causing the liquid film thickness on the protrusions to become thinner, and the area ratio of the thin film portion to exceed 25.0%. If the drying time of the coating is longer, the average area of the thin film portion will exceed 10.0 μm 2Therefore, by increasing the drying temperature as much as possible and shortening the drying time within the range that satisfies the target properties of the film, it is possible to make the area ratio of the thin film part of the organic resin film 25.0% or less. The drying time is preferably 90 seconds or less. Furthermore, by shortening the drying time, it is possible to make the average area of the thin film part 10.0 μm 2 It is also possible to make the drying time shorter than 60 seconds. Therefore, the drying time is more preferably 60 seconds or less. On the other hand, if the drying time is too short, the paint may not spread sufficiently, causing the area ratio of the thin film portion to exceed 25.0%, or the paint may not dry sufficiently, causing deterioration in corrosion resistance. Therefore, the drying time is preferably 2 seconds or more, and more preferably 5 seconds or more.
[0035] The coating property of the organic resin film can be evaluated by measuring the area ratio of the thin film portion of the convex portion using a SEM. Furthermore, the coating property of the organic resin film, which is more advantageous in terms of sliding properties, can be evaluated by measuring the average area of the thin film portion.
[0036] The area ratio and average area of the thin film portion can be measured by evaluating the thin film portion using characteristic X-rays generated by irradiating the sample with an electron beam. Since X-rays have a higher penetrating power than electrons, the accelerating voltage should be set high enough so that the incident electrons can reach the steel substrate even in thick film portions, and the characteristic X-ray image of the CK ray, which is the main constituent element of the organic resin coating, should be measured. As shown in Fig. 1, the area where the CK line intensity is high corresponds to the thick film portion, and the area where the CK line intensity is low corresponds to the thin film portion, so the ratio of the area below a certain threshold value from the characteristic X-ray image can be calculated as the area ratio of the thin film portion. Specifically, the area ratio of the thin film portion is preferably calculated by the following method. (1) At an accelerating voltage of 5 kV or more and 20 kV or less, an X-ray image characteristic of the CK line on the surface of the organic resin-coated steel sheet is taken by an X-ray spectrometer mounted on an SEM. (2) The local adhesion amount was 0.14 g / m from the characteristic X-ray image of CK rays. 2 The area below the threshold intensity corresponding to is defined as the thin film portion, and the area above the threshold intensity is defined as the non-thin film portion. The area of the thin film portion is defined as the area of the thin film portion / (area of the thin film portion+area of the non-thin film portion)×100%.
[0037] The average area of the thin film is 900 μm 2 If the thickness is greater than or equal to the thickness of the film, the area of each thin film portion can be measured and the average value calculated. The individual thin film portions mentioned above refer to each thin film portion, with a thin film portion surrounded by a non-thin film portion being considered as one thin film portion. When evaluating the film thickness uniformity using characteristic X-ray images, observation should be performed at an accelerating voltage of 5 kV or more, which provides a sufficient signal depth for the organic resin film. However, if the accelerating voltage is too high, the efficiency of CK line generation decreases, so it is preferable to observe at an accelerating voltage of 5 kV or more. It is preferable to observe at an accelerating voltage of 10 kV or more. On the other hand, it is preferable to observe at an accelerating voltage of 20 kV or less. The magnification of the characteristic X-ray image used in this evaluation is preferably about 100 to 300 times, which allows observation of the uneven shape caused by rolling and is less affected by distortion at the edges of the screen due to electron beam scanning.
[0038] The threshold strength for calculating the area ratio of the thin film portion was determined to be 0.14 g / m based on the relationship between the coating weight measured separately by gravimetry or other methods and the average intensity of the characteristic X-ray image. 2 The area below the threshold intensity is defined as a thin film portion, and the area above the threshold intensity is defined as a non-thin film portion, and the area ratio of the thin film portion is defined as area of the thin film portion / (area of the thin film portion+area of the non-thin film portion)×100%. When the area ratio of the thin film portion calculated as above is 25.0% or less, the organic resin film coverage is judged to be good.
[0039] The organic resin component is described below.
[0040] The organic resin used in the present invention is not particularly limited, but it is preferable to include at least one of acrylic resin, urethane resin, and phenol resin, because the organic resin exhibits lubrication performance by preventing direct contact between the die and the steel sheet during press molding, and when a hydrocarbon wax is added to the film, the organic resin has a high affinity with the wax, so that a mixture in which the organic resin and the wax are uniformly mixed during sliding is formed, thereby further improving the lubrication performance. The weight ratio of the organic resin to the total weight of the film is preferably 50% or more. The weight ratio of the organic resin to the total weight of the film is more preferably 70% or more. The upper limit is not particularly limited, but it is preferably 100% or less. The ratio of the organic resin described above is the ratio of the total amount of the acrylic resin, urethane resin, and phenol resin contained in the total weight of the film.
[0041] From the viewpoint of the coating environment, it is preferable to use an organic resin component that is soluble or dispersible in an aqueous solvent. Although there are many unknowns regarding the mechanism by which excellent sliding properties are exhibited by forming an organic resin film on a steel sheet, it is believed that the organic resin film contributes to protecting the steel sheet surface during sliding and reducing the sliding resistance.
[0042] In the present invention, the organic resin film may contain wax. The inclusion of wax improves the sliding properties of the film. If the melting point is less than 100°C, the wax melts due to frictional heat caused by sliding during press molding, and sufficient lubrication effect cannot be obtained, so the wax preferably has a melting point of 100°C or higher. The wax more preferably has a melting point of 120°C or higher. On the other hand, the wax preferably has a melting point of 150°C or lower. From the viewpoint of cost and performance, hydrocarbon wax is preferable. The average particle size of the wax is preferably 0.01 μm or more and 4 μm or less. If the average particle size is less than 0.01 μm, the effect of improving the sliding properties may not be exhibited, and the paint stability is also low. Therefore, the average particle size of the wax is preferably 0.01 μm or more. The average particle size of the wax is more preferably 0.2 μm or more. On the other hand, if the average particle size exceeds 4 μm, the wax may not be mixed well into the film during application, and may easily fall off from the coating when handling the steel sheet after application, and the sliding properties may not be exhibited. Therefore, the average particle size of the wax is preferably 4 μm or less. The average particle size of the wax is more preferably 2 μm or less, and even more preferably 1 μm or less.
[0043] The organic resin film desirably contains 50% by mass or less of wax relative to the total film weight, since this improves the lubricating performance. 40% by mass or less is preferable, and 25% by mass or less is more preferable. If the content is too low, the wax will not exhibit its lubricating performance, so the wax mass relative to the total film weight is preferably 5% by mass or more, and more preferably 10% by mass or more.
[0044] The melting point of the wax is the melting temperature measured based on JIS K7121: 1987 "Method of measuring transition temperature of plastics." The average particle shape of the wax is the median diameter of the volume average diameter, and was measured by a laser diffraction / scattering method.
[0045] In the present invention, a surface conditioner for adjusting the surface tension, a defoamer, a dispersant, etc. may be included as components other than the organic resin and the wax. Also, a rust inhibitor for improving rust prevention may be added.
[0046] The dispersant is not particularly limited and any dispersant can be used, but it is preferable to use an anionic polymer dispersant. An anionic polymer dispersant is particularly effective in improving the dispersibility of particles of several μm or less, and can be adsorbed to a hydrocarbon wax. Therefore, the dispersibility of the wax in the paint is improved, and the uniformity of the wax distribution in the obtained film is improved. As a result, the sliding properties are further improved. As the anionic polymer dispersant, it is preferable to use at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer, and sulfonic acid copolymer.
[0047] The proportion of the dispersant in the film is not particularly limited, but is preferably 0.2% by mass or more. When the proportion of the dispersant in the film is 0.2% by mass or more, the dispersibility of the wax in the paint is improved, and the uniformity of the wax distribution in the obtained film is improved. As a result, the sliding properties are further improved. It is more preferable to set it to 0.5% or more, and even more preferable to set it to 1.0% by mass or more. On the other hand, if the proportion of the dispersant in the film exceeds 5.0% by mass, the adhesiveness may deteriorate. Therefore, the proportion of the dispersant in the film is preferably 5.0% by mass or less. It is more preferable to set it to 4.0% by mass or less, and even more preferable to set it to 3.0% by mass or less. Here, the ratio of the dispersant in the coating refers to the ratio of the mass of the dispersant in the coating to the total weight of the coating.
[0048] The effect of the present application is particularly excellent when the surface roughness Ra of the base steel sheet is 0.4 μm to 2.5 μm and the weight ratio of the organic resin to the total weight of the coating is 50 to 100 mass%, so the surface roughness Ra of the base steel sheet and the weight ratio of the organic resin are preferably within the above range. The weight ratio of the organic resin to the total weight of the coating is preferably 50 mass% or more, and more preferably 70 mass% or more. On the other hand, the weight ratio of the organic resin to the total weight of the coating is preferably 100 mass% or less, and more preferably 90 mass% or less. This is because, outside the above range, the paint is likely to accumulate in the recesses of the steel sheet, the coating adhesion amount on the projections is reduced, and the sliding properties are deteriorated, whereas within the above range, the coating adhesion amount on the projections of the steel sheet is sufficient and excellent sliding properties are obtained. Note that the weight ratio of the organic resin to the total weight of the coating is the weight ratio after drying.
[0049] Next, a method for producing a steel sheet according to the present invention will be described.
[0050] The method for producing an organic resin-coated steel sheet of the present invention is a method for producing a steel sheet having an organic resin film on the surface of the steel sheet, which is made of resin or an organic resin film containing wax in a resin. A paint in which a resin is dissolved or dispersed in a solvent, or a paint in which wax has been added to these, is applied to the surface of the steel sheet and then dried. The application method is not particularly limited, and examples include a method using a roll coater or a bar coater, and a coating method using spraying, immersion, or a brush. The steel sheet after coating can be dried by a general method. For example, drying with hot air, drying with an IH heater, or infrared heating can be used. The maximum temperature reached by the steel sheet during drying is preferably 60°C or higher and 150°C or lower. If the temperature is lower than 60°C, drying takes a long time, and the amount of adhesion of the organic resin film varies, resulting in a localized adhesion amount of 0.14 g / m. 2The area ratio of the thin film portion, which is equal to or less than 150°C, increases. Furthermore, the rust prevention properties may be deteriorated. Therefore, the maximum temperature reached during drying is preferably 60°C or higher. More preferably, it is 80°C or higher. On the other hand, if the temperature exceeds 150°C, the film removal properties may be deteriorated. Therefore, the maximum temperature reached during drying is preferably 150°C or lower. More preferably, it is 130°C or lower. As described above, the drying time is preferably 2 seconds or more. The drying time is preferably 90 seconds or less. Methods for controlling the amount of organic resin attached after drying include pressing a rubber roll against the coating material after coating, or controlling the pressing pressure and rotation speed of a roll coater to control the amount of coating material applied.
[0051] Furthermore, since the amount of organic resin attached after drying is also affected by the total solids concentration in the paint, it is preferable to properly adjust the concentration of the paint.
[0052] Here, the area ratio of the thin film portion of the organic resin film is 25% or less, and the average area of the thin film portion is 10.0 μm 2 As a method for determining whether the area ratio is less than 0.1, multiple test pieces (e.g., 3 or more) of a size that can be introduced into an SEM device (e.g., 8 mm square or more and 100 mm square or less) are taken from any location from the organic resin-coated steel sheet manufactured by the above-mentioned manufacturing method, and characteristic X-ray images are obtained from 5 or more fields of view for each test piece under the observation and analysis conditions described above to evaluate the area ratio of the thin film portion and the average area of the thin film portion, thereby obtaining sufficient evaluation accuracy. Note that the threshold value for characteristic X-rays when determining the area ratio of the thin film portion is set to a coating weight of 0.14 g / m2, based on the relationship between the coating coating weight measured separately by gravimetry or the like and the average intensity of the characteristic X-ray images. 2 When the area ratio of the thin film portion that is below this threshold is 25% or less, the steel sheet can be judged to have excellent sliding properties. Furthermore, when the average area of the thin film portion is 10.0 μm 2 When the following conditions are met, the steel sheet can be judged to have excellent sliding properties.
[0053] The calibration curve for determining the characteristic X-ray intensity corresponding to the coating amount utilizes the fact that the NET intensity of the characteristic X-rays is almost directly proportional to the coating amount, and assumes that the coating amount measured by the gravimetric method when the average NET intensity of the characteristic X-rays is 0 is 0, in other words, the intercept is the origin, and uses a straight line connecting the origin and the point obtained by the coating amount measured by the gravimetric method and the average NET intensity of the characteristic X-rays. Here, the NET intensity means the intensity obtained by subtracting the background intensity from the characteristic X-ray intensity.
[0054] The weight of the coating is measured by the gravimetric method, in which the organic resin-coated steel sheet is immersed in an alkaline solution to dissolve only the organic resin portion, and the change in the weight of the steel sheet before and after dissolution is determined. The average intensity of characteristic X-rays is the average value of all data obtained by measuring the area ratio of the thin film portion.
[0055] Although the present invention has been described above based on the embodiment, the present invention is not limited by the description and drawings that form a part of the disclosure of the present invention according to the embodiment. In other words, other embodiments, examples, operation techniques, etc. made by those skilled in the art based on the embodiment are all included in the scope of the present invention. EXAMPLES
[0056] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0057] A cold-rolled steel sheet (TS: 270 MPa) with a thickness of 0.8 mm was cut into a size of 350 mm x 230 mm to be used as a base material for the organic resin coating.
[0058] The cut steel sheets were immersed in a solvent of 50 vol% toluene-50 vol% ethanol, ultrasonically cleaned for 5 minutes, and dried with a blower, and then degreased with an alkaline degreaser Fine Cleaner E6403 (manufactured by Nihon Parkerizing Co., Ltd.). The degreasing treatment consisted of immersing the test pieces in a degreasing solution with a degreaser concentration of 20 g / L and a temperature of 40° C. for 2 minutes, washing with tap water, and then drying with a blower. The paints shown in Table 1 were applied to the steel sheet surface thus prepared with a bar coater, and the steel sheets were baked and dried with induction heating (IH) to produce lubricating organic coated steel sheets shown in Table 2. The temperature at which the coating was baked for each sample is shown in Table 2. The baking temperature refers to the drying temperature. The following evaluations were performed on these samples, and the evaluation results are shown in Table 2.
[0059] The arithmetic mean roughness Ra of the steel plate used was 0.8 μm. The arithmetic mean roughness Ra (μm) of the steel plate can be measured according to JIS B 0633:2001 (ISO 4288:1996). The cutoff value and reference length were 0.8 mm, and the evaluation length was 4 mm.
[0060] [Table 1]
[0061] [Table 2]
[0062] (1) Evaluation method for organic film coating properties The organic film coverage was measured as follows. Five small pieces of 10 mm square were cut from each of the organic resin-coated steel sheets to prepare test materials. A Schottky field emission SEM (Carl Zeiss Σigma) equipped with an energy dispersive X-ray spectrometer (Burker XFlash5|30) was used for the measurements.
[0063] Five characteristic X-ray images were taken from each of the three organic resin-coated steel sheets near the center of the test material at a magnification of 200x. The characteristic X-ray images were CK ray images taken at an accelerating voltage of 15kV. From the characteristic X-ray images, the coating weight was found to be 0.14g / m 2 The area where the CK line intensity was equal to or less than the value of 10.0 μm was defined as the thin film portion, and the area ratio of the thin film portion and the average area of the thin film portion were calculated, and the average values of the 15 fields of view were used for evaluation. 2 The organic resin film coating property is particularly good (◎) when the area ratio of the thin film part is 25% or less and the average area of the thin film part is 10.0 μm or less. 2 When the area ratio of the thin film portion exceeded 25%, the organic resin film coverage was evaluated as good (◯), and when the area ratio of the thin film portion exceeded 25%, the organic resin film coverage was evaluated as poor (×).
[0064] (2) Method for evaluating press formability (sliding characteristics) In order to evaluate the press formability, the friction coefficient of each test material was measured as follows.
[0065] FIG. 2 is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 taken from a test material is fixed to a sample stage 2, and the sample stage 2 is fixed to the upper surface of a horizontally movable slide table 3. A slide table support base 5 that can move up and down and has a roller 4 in contact with the slide table 3 is provided on the lower surface of the slide table 3, and a first load cell 7 is attached to the slide table support base 5 to measure the pressing load N applied by the bead 6 to the friction coefficient measuring sample 1 by pushing it up. A second load cell 8 is attached to one end of the slide table 3 to measure the sliding resistance force F for moving the slide table 3 in the horizontal direction while the pressing force is applied. The test was performed by applying press cleaning oil Pleton R352L manufactured by Sugimura Chemical Industry Co., Ltd. as a lubricant to the surface of the sample 1.
[0066] Figure 3 is a schematic perspective view showing the shape and dimensions of the bead used. The underside of the bead 6 slides while being pressed against the surface of the sample 1. The shape of the bead 6 shown in Figure 3 is 10 mm wide, 59 mm long in the sliding direction of the sample, and the lower parts of both ends in the sliding direction are curved surfaces with a curvature of 4.5 mmR, and the underside of the bead against which the sample is pressed has a flat surface with a width of 10 mm and a length of 50 mm in the sliding direction.
[0067] The friction coefficient measurement test was performed using the bead shown in Figure 3, with a pressing load N of 400 kgf and a sample pull-out speed (horizontal movement speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the test material and the bead was calculated by the formula μ = F / N. A friction coefficient of 0.080 or less was evaluated as being particularly good sliding characteristics, with an ⊚ mark, while a friction coefficient of 0.130 or less was evaluated as being good sliding characteristics, with a coefficient of more than 0.130 being evaluated as being insufficient and marked as ×.
[0068] (3) Evaluation method for film removal To determine the removability of the organic resin-coated steel sheet, each test piece was first degreased with an alkaline degreaser, Fine Cleaner E6403 (manufactured by Nippon Parkerizing Co., Ltd.). This treatment consisted of immersing the test piece in a degreaser with a concentration of 20 g / L and a temperature of 40° C. for a predetermined period of time, rinsing with tap water, and then drying with a blower. The surface carbon intensity of the test piece after this treatment was measured using an X-ray fluorescence analyzer, and the coating peeling rate was calculated according to the following formula using this measurement value, the previously measured surface carbon intensity before degreasing, and the measured surface carbon intensity of the untreated steel sheet.
[0069] The removability of the organic resin-coated steel sheet was evaluated according to the following criteria, based on the immersion time in the alkaline degreasing solution at which the film peeling rate reached 98% or more. <Coating peeling rate> Film peeling rate (%) = [(carbon strength before degreasing - carbon strength after degreasing) / (carbon strength before degreasing - carbon strength of untreated steel plate)] x 100 <Evaluation criteria> ◎Good: within 60 seconds Applicable range: Over 60 seconds and up to 120 seconds × Not applicable: More than 120 seconds
[0070] (4) Weldability evaluation method For each test piece, a continuous welding test was performed under the following conditions: electrode used: DR type Cr-Cu electrode, pressure: 150 kgf, current application time: 10 cycles / 60 Hz, welding current: 7.5 kA, and the welding performance was evaluated based on the number of continuous welding points. The evaluation criteria were as follows: <Evaluation criteria> Excellent: 5000 points or more × Poor: Less than 5000 points
[0071] (5) Overall evaluation of the coating For each test piece, if the evaluation in (4) above was ◯, the evaluation in (3) above was ◎ or ◯, and the evaluations in (1) and (2) above were ◎, it was marked as pass (excellent): ◎; if the evaluation in (4) above was ◯, the evaluation in (3) above was ◎ or ◯, and the evaluations in (1) and (2) above were ◯, it was marked as pass (fair): ◯; and if any one or more of the evaluations in (1) to (4) above was ×, it was marked as fail: ×.
[0072] From the evaluation results in Table 2, all of the examples of the present invention were evaluated as ◯ or ◎ in overall rating, and it was possible to obtain an organic resin-coated steel sheet having excellent press formability, as well as excellent removability and weldability. In particular, when the overall rating was ◎, it was possible to obtain an organic resin-coated steel sheet having even better press formability. [Industrial Applicability]
[0073] The organic resin-coated steel sheet of the present invention has excellent press formability and weldability, and also has a wide range of applicability including removability, and therefore can be used in a wide range of fields, primarily in automobile body applications. [Explanation of symbols]
[0074] 1. Sample for measuring friction coefficient 2 Sample stage 3 Slide table 4. Lola 5 Slide table support 6 Beads 7 First load cell 8 Second Load Cell 9. Rail
Claims
1. An organic resin film is applied to at least one side, with the average adhesion amount per side after drying being 0.2 g / m 2 2.0g / m or more 2 A steel sheet coated as follows: The organic resin film had a coating weight of 0.14 g / m 2 the area ratio of a thin film portion satisfying the following formula is 14.0% or more and 25.0% or less, the organic resin coating is a coating containing one or more of an acrylic resin, a urethane resin, and a phenolic resin, and the friction coefficient is 0.129 or less.
2. The average area of the thin film portion is 10.0 μm 2 The organic resin-coated steel sheet according to claim 1 , wherein:
3. 2. The organic resin-coated steel sheet according to claim 1, wherein the area ratio of the thin film portion is calculated by the following methods (1) and (2). (1) A characteristic X-ray image of the C-K line of the surface of the organic resin-coated steel sheet is taken by an X-ray spectrometer mounted on an SEM at an accelerating voltage of 5 kV or more and 20 kV or less. (2) The local adhesion amount from the C-K characteristic X-ray image was 0.14 g / m 2 The area below the threshold intensity corresponding to is defined as a thin film portion, and the area above the threshold intensity is defined as a non-thin film portion, and the area ratio of the thin film portion is defined as area of the thin film portion / (area of the thin film portion+area of the non-thin film portion)×100%.
4. 3. The organic resin-coated steel sheet according to claim 2, wherein the area ratio of the thin film portion is calculated by the following methods (1) and (2). (1) A characteristic X-ray image of the C-K line of the surface of the organic resin-coated steel sheet is taken by an X-ray spectrometer mounted on an SEM at an accelerating voltage of 5 kV or more and 20 kV or less. (2) The local adhesion amount from the C-K characteristic X-ray image was 0.14 g / m 2 The area below the threshold intensity corresponding to is defined as a thin film portion, and the area above the threshold intensity is defined as a non-thin film portion, and the area ratio of the thin film portion is defined as area of the thin film portion / (area of the thin film portion+area of the non-thin film portion)×100%.
5. 5. The organic resin-coated steel sheet according to claim 1, wherein the organic resin coating contains 50 mass % or less of wax based on the total coating weight.
6. 6. The organic resin-coated steel sheet according to claim 5, wherein the wax is a hydrocarbon wax.
7. 6. The organic resin-coated steel sheet according to claim 5, wherein the wax has an average particle size of 0.01 μm or more and 4 μm or less.
8. 7. The organic resin-coated steel sheet according to claim 6, wherein the wax has an average particle size of 0.01 μm or more and 4 μm or less.
9. 6. The organic resin-coated steel sheet according to claim 5, wherein the organic resin coating contains 5.0 mass% or less of an anionic polymer-type dispersant based on the total coating weight.
10. 7. The organic resin-coated steel sheet according to claim 6, wherein the organic resin coating contains 5.0 mass % or less of an anionic polymer-type dispersant based on the total coating weight.
11. The organic resin-coated steel sheet according to claim 7 , wherein the organic resin coating contains 5.0 mass % or less of an anionic polymer-type dispersant based on the total coating weight.
12. The organic resin-coated steel sheet according to claim 8 , wherein the organic resin coating contains 5.0 mass % or less of an anionic polymer-type dispersant based on the total coating weight.
Citation Information
Patent Citations
Galvanized steel sheet covered with alkali-soluble resin coating film having excellent adhesiveness by adhesive
JP1997170059A
Production of resin-coated steel sheet
JP1998290953A
Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property
JP2000167981A
Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition
JP2000309747A
Lubricating-treated steel panel excellent in chemical forming treatment properties and adhesiveness
JP2002307613A